Síntese e caracterização de compostos de Ru3+ com ligantes : Glicina e Guanina e avaliação do efeito antitumoral - Chagas, Marcio Adriano Sousa (2015)
Since the 1970s is used metal complexes, such as cisplatin™ in chemotherapy treatments, but even today there still a lack of knowledge on the mechanism of action of biologically active metal complexes that are used in traditional medicine or pharmaceutical. Ruthenium compounds in the oxidation states Ru2+ and Ru3+ are under investigation where good results have been regarding the low cytotoxicity on normal cells and efficient cytotoxic activity in tumor cells. This work presents the synthesis, characterization and application in an anti-tumor bioassay of a new Ru3+ compound containing NH2CH2COO-, C5H5N5O, H2O e Cl- in order to reduce the cytotoxicity of currently used drugs. The compound was synthesized and characterized by UV-VIS spectroscopy, with peaks at 290 nm and absorption spectroscopy by Fourier transform infrared medium spectroscopy (FTIRmed), demonstrating vibrational bands characteristic of the binders: a(COO-)1664 cm-1, s(COO-) 1388 cm-1, s(NH3+) 1571 cm-1, s(CCN) 889 cm-. The 13C and 1H NMR spectra showed the chemical shifts regarding glycine ligand groups to COOH (δc 172,6), CH2 (δc 41,69 e δH 3,45 ppm), and NH2 (δH 4,64 – 4,71 ppm). The complex was studied by thermoanalytical techniques (TG/DTG and TG-DTA), and a critical evaluation of the curves indicated that thermal decomposition occurred in four steps: thermal dehydration occurred at 115°C (TG=12.18%; Calcd=11.32%) and 665ºC. The residue was composed of RuClO (TG= 41.11%; Calcd=40.81%), confirming the stoichiometry of the compound Bis-aquo-trichlorine-glycinerutheniumIII [RuCl3(H2O)2Gly]. We performed the synthesis of the complex [RuCl3(H2O)2Gly] with guanine (C5H5N5O), DNA base, where the complex interaction was observed by UV-VIS spectroscopy peaks at 244 and 272 nm differentiating the starting complex spectrum. Through of FTIRmed spectroscopy was observed guanine interaction with the complex by variations between the symmetric vibration δs(N7-N9) 1435 cm-1 and asymmetric δas(N7-N9) 1260 cm-1 its imidazole group. To evaluate the characteristics of the crystal, XRD analysis was performed indicating the crystalline character of the compound. Antitumor assay was performed to evaluate the activity of the complex [RuCl3(H2O)2Gly] in tumor cell linesS-180, Ehrlich, D-17 and normal L929 where it was observed that the low cytotoxic activity towards tumor cells and normal.